The Contribution of the Internal Audit Function, Audit Committee, and External Auditor Quality in Shortening Audit Report Lag in the Pre- and During-COVID-19 Pandemic Era - Fauzia, Syifa; Rosidi (TEMA, 2025)
Delay in submitting annual financial reports is still a phenomenon in companies going public. The large number of audit report lag phenomena makes companies need to find ways to shorten it. This study aims to determine the effect of internal audit function, audit committee, and external auditor quality on audit report lag before and during the COVID-19 pandemic. This study applies a causal associative design through a quantitative approach. The population includes consumer services sub-sector companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2022, from which the samples of 132 observable data from 22 companies are selected through purposive sampling. The results of the multiple linear regression analysis utilizing SPSS 26.0 exhibit that the internal audit function and audit committee have no effect on audit report lag, both before and during the Covid-19 pandemic, while the external auditor quality has a significant effect on audit report lag during the Covid-19 pandemic.